Anomalous Kondo resonance mediated by semiconducting graphene nanoribbons in a molecular heterostructure. Issue 1 (December 2017) - Li, Yang; Ngo, Anh T.; DiLullo, Andrew; Latt, Kyaw Zin; Kersell, Heath; Fisher, Brandon; Zapol, Peter; Ulloa, Sergio E.; Hla, Saw-Wai
Abstract Kondo resonances in heterostructures formed by magnetic molecules on a metal require free host electrons to interact with the molecular spin and create delicate many-body states. Unlike graphene, semiconducting graphene nanoribbons do not have free electrons due to their large bandgaps, and thus they should electronically decouple molecules from the metal substrate. Here, we observe unusually well-defined Kondo resonances in magnetic molecules separated from a gold surface by graphene nanoribbons in vertically stacked heterostructures. Surprisingly, the strengths of Kondo resonances for the molecules on graphene nanoribbons appear nearly identical to those directly adsorbed on the top, bridge and threefold hollow sites of Au(111). This unexpectedly strong spin-coupling effect is further confirmed by density functional calculations that reveal no spin–electron interactions at this molecule-gold substrate separation if the graphene nanoribbons are absent. Our findings suggest graphene nanoribbons mediate effective spin coupling, opening a way for potential applications in spintronics. Semiconducting graphene nanoribbon provides a platform for band-gap engineering desired for electronic and optoelectronic applications. Here, Li et al. show that graphene nanoribbon can effectively mediate the interaction of molecular magnetic moment and electronic spin in underlying metallic substrates.